PENGARUH KOMPETENSI SUMBER DAYA MANUSIA DAN PENERAPAN SISTEM AKUNTANSI KEUANGAN DAERAH TERHADAP KUALITAS LAPORAN KEUANGAN DAERAH KABUPATEN GIANYAR - I Wayan Juniartha; Gde Herry Sugiarto Asana (Journal Research of Accounting, 2020)
This study aims to determine the effect of human resource competence and the application of regional financial accounting systems to the quality of financial statements in the Gianyar Regency, both partially and simultaneously, the number of employees used as samples in this study amounted to 45 people, the data used in this study are Primary data distributed through questionnaires. The results showed that partially or simultaneously human resource competency (X1) and the application of the regional financial accounting system (X2) had a positive effect on the quality of regional financial reports. The magnitude of the influence of human resource competence and the application of the regional financial accounting system by 54.4% while the remaining 45.6% is explained by other variables outside this research model.